1990
DOI: 10.1016/0736-5748(90)90014-s
|View full text |Cite
|
Sign up to set email alerts
|

Cortical neuron sensitivity to neurotransmitters following neonatal noradrenaline depletion

Abstract: In order to test the functional significance of rapid eye movement (REM)-sleep and noradrenergic activity for cerebral cortex maturation, rat pups were daily injected with clonidine from 8 to 21 days of life. Previous studies have shown that this treatment reduces the amount of time spent in REM-sleep and the level of noradrenaline turnover in the brain. For long-term consequences of such treatment in adulthood, cortical neuron responses to micro-iontophoretically applied neurotransmitters were studied. No sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…A proportional reduction of tissue protein was also found in the affected brain areas [33]. Neurotransmitter circuitry was also modified: in the cerebral cortex, the level of the gamma-aminobutyric-acidergic (GABAergic) depression of the glutamate-induced single cortical neurons responses was greater in the neonatally REM sleep-deprived rats as compared to controls [35,36], while there was a hyper-sensitivity of the pyramidal cells to noradrenalin in the hippocampus [37].…”
Section: Rem Sleepmentioning
confidence: 83%
“…A proportional reduction of tissue protein was also found in the affected brain areas [33]. Neurotransmitter circuitry was also modified: in the cerebral cortex, the level of the gamma-aminobutyric-acidergic (GABAergic) depression of the glutamate-induced single cortical neurons responses was greater in the neonatally REM sleep-deprived rats as compared to controls [35,36], while there was a hyper-sensitivity of the pyramidal cells to noradrenalin in the hippocampus [37].…”
Section: Rem Sleepmentioning
confidence: 83%
“…We have pursued these structural changes at the functional level and found, in adulthood, changes in the neurotransmitter circuitry of neonatally REM deprived animals. In the cerebral cortex the magnitude of the GABAergic depression of the glutamate induced single cortical neurons responses was greater in the neonatally REM deprived rats [59,60]. In the hippocampus there was a supersensitivity of the pyramidal cells to noradrenaline [61].…”
Section: Rem Sleep and Brain Developmentmentioning
confidence: 95%
“…Like serotonin, noradrenergic axons make contact with the Cajal Retzius cells in the marginal zone, suggesting a role in the laminar formation of cortical regions [ 132 , 142 , 143 ]. In addition, noradrenalin seems to have an effect on the development of dopaminergic projections in the PFC by providing a dopamine reuptake mechanism through the noradrenalin transporter [ 144 , 145 ] as well as on GABAergic signaling in the PFC [ 146 , 147 ]. Recent studies of rat and primate PFC showed that the α2-adrenoceptor and muscarinic M1 receptor modulate working memory via KCNQ potassium channel [ 148 151 ].…”
Section: The Early Stages Of Pfc Developmentmentioning
confidence: 99%